A NEW EXPERIMENTAL SETUP FOR STUDYING THE FORMATION OF PHOSPHATE BINDING IRON OXIDES IN MARINE SEDIMENTS. PRELIMINARY RESULTS - Matthiesen H.; Leipe T.; Laima M.J.C. (My University, 2001)
A new laboratory method is introduced to study theformation of phosphate binding iron(III) oxides at theredox boundary in marine sediments. A sediment core isgiven a very well-defined oxic-anoxic interface byplacing a 0.45 µm filter between the sediment andthe overlying water. After a period of 1.5 months thefilter is covered with a layer of fresh iron oxides,formed by the oxidation of upward diffusing Fe2+from the sediment pore water. The formed iron oxidesare investigated by electron probe X-ray microanalysis(EXPMA). With a sediment core from the brackish BalticSea the average molar composition of 788 formedparticles is Fe1.00±0.13P0.55±0.06Ca0.37±0.04 plus unknown amounts of O, H andC. The results show that the particles have a uniformcomposition, and that calcium plays an important rolein the phosphate binding. The laboratory method is auseful supplement to in situ sampling forstudies of iron oxides.